2011
DOI: 10.4067/s0718-58392011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ORYZA2000 Rice Growth Model under Nitrogen-Limited Conditions in an Irrigated Mediterranean Environment

Abstract: ORYZA2000 is a growth model for tropical lowland rice (Oryza sativa L.) developed by the International Rice Research Institute and Wageningen University. This model has been evaluated extensively in a wide range of environments. However, reports examining japonica cultivars growing in temperate climates are scarce. In this study, ORYZA2000 was calibrated and evaluated using data from experiments carried out in the South-Central area of Chile. These experiments were performed on a japonica rice cultivar growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…For dry matter and grain yield, the RMSE and NRMSE of the SimulArroz model varied from 0.6 to 1.0 Mg ha -1 and from 6.3 to 8.3%, respectively (Figure 2 E). Tang et al (2009) and Artacho et al (2011) achieved RMSE values ranging from 0.6 to 1.6 Mg ha -1 and a NRMSE of 19%, slightly higher than those obtained by the SimulArroz model for grain yield in the present study.…”
Section: Resultscontrasting
confidence: 76%
“…For dry matter and grain yield, the RMSE and NRMSE of the SimulArroz model varied from 0.6 to 1.0 Mg ha -1 and from 6.3 to 8.3%, respectively (Figure 2 E). Tang et al (2009) and Artacho et al (2011) achieved RMSE values ranging from 0.6 to 1.6 Mg ha -1 and a NRMSE of 19%, slightly higher than those obtained by the SimulArroz model for grain yield in the present study.…”
Section: Resultscontrasting
confidence: 76%
“…During the 1980's, the yield was predicted based on the past years' yield scenario and the current weather conditions [84]. The yield prediction can be significantly improved by including the knowledge of field level soil moisture and plant health status during the growing season [85]- [86]. It has been identified that LAI, fresh biomass, plant water content, and height indicates the plant health status.…”
Section: E Crop Yieldmentioning
confidence: 99%
“…Mostly, researchers use one set of carefully calibrated parameters either with data from several years or several specific treatments, and validate it with data for other years or other treatments. Mostly, researchers use one set of parameters calibrated either with data from several years (Shuai et al, 2009;Li et al, 2011) or several specific treatments (Jing et al, 2007;Zhang et al, 2007;Amiri and Rezaei, 2010;Artacho et al, 2011) and validate it with data for other years or treatments. For example, Li et al (2011) calibrated ORYZA with data under continuous flooding irrigation and validated it with data under alternated wetting and drying irrigation regimes.…”
Section: Introductionmentioning
confidence: 99%